COMPARATIVE ANALYSIS OF COMMUNICATION STRATEGIES IN BUSINESS DISCOURSE OF ENGLISH AND UZBEK LANGUAGES - Qodirova Mukaddas Togayevna (Scholar Express Journal, 2024)
In the current era of globalization, the impact of language changes and communication strategies driven by this phenomenon is highly significant. Business discourse, especially in cross-linguistic communication, can differ. This article highlights the comparison of communication strategies in business discourse in English and Uzbek, emphasizing their distinctive features and differences. The paper also discusses practical aspects of language use, such as styles, traditions, decision making processes, and the use of language in business contexts. The goal is to lay the groundwork for a more effective and comprehensible understanding of business communication strategies across different languages. This comparison is also expected to help strengthen intercultural relationships and cooperation.
Keywords: Business Discourse; Politeness Strategies